An innovation management assessment framework. Issue 5 (14th May 2020) - Lobo, Stanislaus; Samaranayake, Premaratne
Abstract : Purpose: This paper proposes an integrated approach for assessing innovation management practices using an innovation management assessment framework, with the application of the innovation management assessment framework at the incubation and firm level. Design/methodology/approach: Innovation management assessment framework is developed, based on the literature review. An innovation management assessment framework toolkit for training innovation practitioners is proposed as the basis for the framework implementation in the industry. The main approach is to make close alignment of the design for lean six sigma phases within broader innovation and stage-gate model in the innovation management assessment framework. Findings: The operationalization of the innovation management assessment framework is enabled and supported by an assessment framework and a toolkit for managing innovation. Practical implications: A roadmap for innovation management and assessment of performance at incubatee/firm level. Social implications: It provides a tool for developing innovative products and services for incubatees in start-ups, thus fueling the economy. It also has applications for ongoing established businesses. Originality/value: Innovation of new business development can be made through a well-designed and implemented innovation programme that is aligned with stage-gate and design for lean six sigma phases through the innovation management assessment framework.